Pengaruh Motivasi Dan Partisipasi Petani Terhadap Tingkat Keberhasilan Program Unit Pengolahan Pupuk Organik (UPPO) - Desfiansyah, Rezki (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
The purpose of the this research is to know: (1). The Influence of Farmer Motivation and Participation on the Success Rate of the Organic Fertilizer Processing Unit Program (UPPO), (2). The Influence of Farmer Motivation on the Success Rate of the Organic Fertilizer Processing Unit Program (UPPO), (3). The Influence of Farmer Participation on the Success Rate of the Organic Fertilizer Processing Unit Program (UPPO). This research was conducted at Farmers Group Sumber Sri Asih in Wanguk Village, Anjatan Subdistrict, Indramayu Regency in July-September 2019. Using survey method in farmer group who got UPPO Program, with questionnaire as a tool to know information from the respondent. The data used in this research are primary data and secondary data. The results showed that: (1). The collectively, Farmer Motivation And Participation, there is a positive and significant influence on the Success Rate of the Organic Fertilizer Processing Unit Program (UPPO). (2). There is a positive dan significant influence of Farmer Motivation on the Success Rate of the Organic Fertilizer Processing Unit Program (UPPO), (3). There is a positive and significant influence of Farmer Participation on the Success Rate of the Organic Fertilizer Processing Unit Program (UPPO).